2017
DOI: 10.4172/2329-9096.1000440
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Injuries in British Army Recruits: A Retrospective Study of Incidence and Training Outcome in Different Infantry Regiments Over Five Consecutive Training Years

Abstract: Background: Musculoskeletal training injuries represent a considerable socio economic burden with far reaching implications on organisational effectiveness. Injury data analysis is fundamental to understanding the magnitude of the problem and underpins the subsequent design and delivery of targeted prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…This is especially true of overuse (CMT) injuries in physically active populations. Yet CMT injuries have long been acknowledged as having a substantial impact to military populations, 9,13,[19][20][21][22][23][24][25][26][27][28][29] to civilians especially in certain occupational settings 1,2,5,34 and in athletic communities. [6][7][8]35 For example, in 1995 the sports medicine community noted "a dramatic rise in what is called 'overuse injury'.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This is especially true of overuse (CMT) injuries in physically active populations. Yet CMT injuries have long been acknowledged as having a substantial impact to military populations, 9,13,[19][20][21][22][23][24][25][26][27][28][29] to civilians especially in certain occupational settings 1,2,5,34 and in athletic communities. [6][7][8]35 For example, in 1995 the sports medicine community noted "a dramatic rise in what is called 'overuse injury'.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Military studies have indicated that overuse injuries are a leading military medical burden, annually costing millions in medical treatment and lost duty time. 19,[21][22][23][26][27][28]38 Inclusion of these injuries in military injury surveillance is therefore critical to ensure a full understanding of their impact to force readiness. However, MSKI and especially CMT MSKI, have not been consistently defined or reported -or compared in the context of injuries from all other external causes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations